2015
DOI: 10.12973/eu-jer.4.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Discrepancy between Learner and Teacher Beliefs: What should be the Role of Grammar in Language Classes?

Abstract: Learner and teacher beliefs play an important role in second language (L2) learning. Furthermore, the role of grammar instruction and error correction in the L2 classroom is a topic that is still debated in the literature. This study explored the beliefs of EFL learners and teachers regarding the controversial role of grammar instruction and error correction. A total of 17 instructors and 60 students at a private Turkish university participated in the study. The participants completed an open-ended questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Despite the emphasis on learning grammar to pass exams, participants believed that grammar was essential for skills development and international English tests. Thus, their beliefs were consistent with the positive attitude that EFL students in South East Asia (e.g., Deng & Lin, 2016;Saengboon, 2017) and other regions (e.g., Hos & Kekec, 2015;Graus & Coppen, 2016) held about grammar in previous studies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Despite the emphasis on learning grammar to pass exams, participants believed that grammar was essential for skills development and international English tests. Thus, their beliefs were consistent with the positive attitude that EFL students in South East Asia (e.g., Deng & Lin, 2016;Saengboon, 2017) and other regions (e.g., Hos & Kekec, 2015;Graus & Coppen, 2016) held about grammar in previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, EFL learners have been reported to acknowledge the indispensable role of grammar. For instance, Hos and Kekec (2015) found in their qualitative findings that most university Turkish students perceived grammar as essential. Likewise, Thai university students believed it was necessary to learn grammar (Saengboon, 2017).…”
Section: Revisitingviewsofgrammarandgrammarlearningstrategyuse:amulti...mentioning
confidence: 99%
“…This discussion revealed that between teachers and student-teachers had same preferences by arguing integrated teaching grammar approach was the most suitable teaching grammar approach. This last finding was supported by four previous studies who found that between teachers and student-teachers, they have same preferences in teaching grammar which is integrated teaching grammar approach (Ahmad et al, 2017;Deng & Lin, 2016;Hos & Kekec, 2015;Valeo & Spada, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…Another previous research was conducted to find the role of grammar in language class. It was done by Hos and Kekec (2015) conducting a study about the differences between teachers" and student-teachers" views about grammar in language class. A total of 17 tutors and 60 pre-service teachers at private university in Turkish partaken in this study.…”
Section: Teaching Grammar In Contextmentioning
confidence: 99%
“…Findings demonstrated the students 'grammar skills handling, oral and positive attitudes. Hos & Kekec (2015) investigated the views of EFL students and teachers on the controversial role of grammatical instruction and the correction of errors. This research shows that both students and teachers agreed that language grammar and error correction were important; however, there were some gaps between students and teachers in the use of language in grammar and other areas of grammar teaching.…”
Section: B2 Communicative Grammar Instruction In Efl/esl Classesmentioning
confidence: 99%